Analisa Pengaruh Struktur Modal, Pertumbuhan Perusahaan, Ukuran Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2015 - Hanifah, Nunung Nur; , Muzakar Isa, S.E., M.Si (2017)
The purpose of this study to analyze the influence of the capital structure, the company's growth, company size and profitability of the value of banking companies listed on the Indonesian Stock Exchange 2011-2015 period. The data used are secondary data from company financial statements derived from the annual financial statements (annual report) that has been published through the official website IDX. The determination of this sample using purposive sampling method based on certain criteria. From this method obtained 22 banking companies that meet the criteria established. The amount of data used for the study at 94 with 5-year study period. Methods of data analysis using multiple linear analysis. Based on the partial results of research known that the capital structure and no significant positive effect on firm value. While the company's growth, company size and profitability and significant positive effect on firm value. While simultaneously the capital structure, the company's growth, company size and profitability and significant positive effect on firm value. Variable value of the company can be explained by the variable capital structure, the company's growth, company size and profitability of 35.5%, while the remaining 64.5% is explained by other variables.